Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf00717002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of pancreatic spasmolytic polypeptide (PSP) in the pig

Abstract: Pancreatic spasmolytic polypeptide (PSP) is a peptide that is isolated from the porcine pancreas and that affects intestinal motility and growth of intestinal tumour cells in vitro. The peptide was recently demonstrated to be present in large amounts in pancreatic juice. The cellular origin of the peptide, however, is largely unclarified and the localization was therefore studied of PSP in pigs using immunohistochemistry. Positive immunoreactions were seen in the pancreas, the stomach, the duodenum, the jejunu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…In pigs TFF2 is apparently expressed on the entire luminal surface of the gastrointestinal tract at rather high concentrations [25]. Expression of TFF2 in vivo has been documented in various organisms, each having a unique tissue specific pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pigs TFF2 is apparently expressed on the entire luminal surface of the gastrointestinal tract at rather high concentrations [25]. Expression of TFF2 in vivo has been documented in various organisms, each having a unique tissue specific pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in porcine gastric tissue, however, are concordant to high protein expression of TFF2 in the stomach reported in other species. In a previous study with pigs by Rasmussen et al, immunostaining revealed TFF2 expression in pancreas, in mucous cells of the glands of the stomach, in Brunner's glands of the duodenum, and in epithelial cells of the crypts of Lieberkühn in the jejunum and ileum, but not in duodenal goblet cells [25]. Localization of TFF2 in this study is in agreement with the studies by Rasmussen et al in terms that goblet cells of the intestinal epithelium did not express TFF2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, porcine pancreatic TFF2 forms non-covalently linked dimers in the solid phase (9,11) as well as in solution (12); the latter being unusually resistant even to boiling SDS (12). TFF2 is typically co-secreted with the mucin MUC6 from gastric fundic and antral glands (mucous neck and antral gland cells, respectively) as well as duodenal Brunner's glands (13)(14)(15)(16)(17) and represents a characteristic constituent of the gastroduodenal mucus (18). Of special note, in the gastric fundic glands TFF2 mRNA and protein do not co-localize.…”
Section: Tff2 a Muc6-binding Lectin Stabilizing The Gastric Mucus Bamentioning
confidence: 99%
“…TFF2 also appears as a constituent of the gastric juice with dramatic diurnal variations (22). In the pig, in contrast to human, TFF2 is also abundantly secreted from exocrine pancreatic glands (acinar cells) (14). Furthermore, TFF2 is expressed in salivary glands (21,23).…”
Section: Tff2 a Muc6-binding Lectin Stabilizing The Gastric Mucus Bamentioning
confidence: 99%